REE Distribution in Lake Van Stromatolites: Detrital vs. Authigenic Signature - Sasmaz, Bilge; Cangemi, Marianna; Oliveri, Ygor; Sasmaz, Ahmet (Mdpi, 2026)
Lake Van (Eastern Turkey), the world's largest soda lake, represents a unique geochemical environment characterized by high alkalinity (pH about 9.7) and a complex hydrochemistry, driven by deep hydrothermal input and extreme evaporative processes. This article evaluates mineralogy, minor elements, and Rare Earth Element (REE) geochemistry of coastal stromatolites from 11 sites, to discriminate between endogenous chemical signals and terrigenous contamination. Results identify two distinct lithological groups: a chemically pure authigenic end-member (CaCO3 > 85%), overprinted by a significant siliciclastic detrital contribution, rich in SiO2, Al2O3, and Fe2O3. Authigenic samples successfully preserve the primary hydrothermal signature, exhibiting marked Heavy Rare Earth Element (HREE) enrichment and superchondritic Y/Ho ratios (=35), inherited from the stability of dissolved dicarbonate complexes, such as [REE(CO3)(2)](-), which favor HREE solubility and uptake into the carbonate lattice. Conversely, the significant detrital contribution is highlighted by a robust correlation between REE and lithogenic proxies (Al-Si-Fe). Furthermore, the non-CHARAC behavior observed in Y/Ho and Zr/Hf twin pairs effectively distinguishes biogenic-chemical precipitation from detrital inputs. These results highlight the effectiveness of REE geochemistry as a proxy to filter out lithogenic overprints and accurately isolate the primary hydrochemical record of carbonate stromatolites.
Keywords: stromatolites; Lake Van; rare earth elements; Y/Ho and Zr/Hf twin pairs